Disinfection effect of microwave radiation on Bacillus subtilis as indicator organism on contaminated dental stone casts under dry and wet conditions - Robati Anaraki, Mahmood; Mahboubi, Shiva; Pirzadeh, Tahereh; Lotfipour, Farzaneh; Torkamanzad, Naimeh (German Medical Science GMS Publishing House, 2017)
Objective: The disinfection of dental stone casts using microwave radiation has been shown, but doubts remain regarding its efficacy under various conditions. The aim of the present study was to evaluate the efficacy of microwave disinfection on wet and dry dental stone casts contaminated by a resistant microorganism. Material and methods: In this in vitro study, 34 stone half-casts were prepared, contaminated with and divided into two groups. After drying the specimens of one group for 15 minutes using 450 W microwave energy, all the wet and dry specimens were exposed to 900 W microwave energy for 5 minutes. Specimens were then individually transferred to nutrient broth culture medium and after , one milliliter from each tube was cultured in nutrient agar media for 24 hours, and the colonies were counted in CFU/mL. Data were analyzed using multifactorial ANOVA and Bonferroni tests.Results: Casts in both wet and dry groups were disinfected to a high level (6 log), with no statistically significant differences between them (P<0.05). Conclusion: According to the results, microwave irradiation can disinfect dental stone casts to a high degree, irrespective of moisture level. However, the result should be confirmed by exploring with other species of resistant microorganisms.